A global comparison of the climatic niches of urban and native tree populations. Issue 5 (1st March 2018) - Kendal, Dave; Dobbs, C.; Gallagher, R. V.; Beaumont, L. J.; Baumann, J.; Williams, N. S. G.; Livesley, S. J.
Abstract: Aim: Urban macroecology studies can provide important insights into the impacts of climate change and human intervention in ecosystems. Current theory predicts that urban trees are constrained by temperature in very cold climates but not in other climates. Here we predict the climatic niche variables of planted urban tree populations from the realized climatic niche of native populations and explore whether niches are constrained across all temperatures. Location: Global (182 cities across six continents). Time period: Urban tree data: 1980–2016. Native tree data: 1950–2017. Major taxa studied: Two hundred and three tree species. Methods: We used urban tree inventory data and Global Biodiversity Information Facility occurrence data to compare the realized climatic niches of native and urban tree populations. Realized climatic niches are calculated by combining bioclimatic data with native tree and urban tree occurrence data. Regression is used to predict the climatic niche of urban tree populations from the climatic niche of native populations. Results: The realized climatic niche of native tree populations was a good predictor of the realized climatic niche of urban tree populations, although climatic niches are attenuated in urban populations. Urban tree niches were 38–90% wider than native tree niches, with the mean annual temperature niche breath of urban tree populations 3.3 °C (52%) wider than native tree populations. Main conclusions: Urban trees are planted in climates that are outside the realized climatic niche of native populations. Temperature remains a strong filter on urban tree populations across the full temperature range. Temperature increases attributable to the combined effect of the urban heat island and global climate change are likely to have a substantial impact on urban tree populations around the globe. This is particularly true for temperate cities, where cold climate trees are planted near the upper limits of their realized temperature niches.